Resin composition with high speed and low expansion coefficient as well as preparation method and application thereof

By using methacrylate-based modified polyshenol resin, prepolymer and accelerator in the resin composition of the printed circuit board, a cured substance with a low expansion coefficient and a low dielectric constant is formed, and the problem of insufficient performance of the printed circuit board substrate material under high density and multilayer conditions in the prior art is solved, and high heat resistance and good processing performance are achieved.

CN119708740APending Publication Date: 2025-03-28CHENZHOU GONGTIAN ELECTRONICS CERAMICS TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411916339.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Under high density and multilayer conditions, the substrate materials of existing printed circuit boards are difficult to meet the requirements of high heat resistance, low thermal expansion coefficient and low dielectric constant, especially in terms of thermal expansion coefficient (Z direction) and XY-CTE.

Method used

Using a resin composition, the composition comprises 20-60 parts of methacrylate-based modified polyshenol resin, 40-80 parts of prepolymer and 0.05-2 parts of accelerator, a cured product with a low coefficient of expansion, a low dielectric constant and a high heat resistance is formed by crosslinking with the prepolymer.

Benefits of technology

It is achieved that the thermal expansion coefficient and dielectric constant of the printed circuit board are significantly reduced without increasing the filler volume, while maintaining good processing performance and heat resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119708740A_ABST
    Figure CN119708740A_ABST
Patent Text Reader

Abstract

The invention discloses a resin composition which comprises the following components in parts by weight: 20-60 parts of a compound A, 40-80 parts of a prepolymer B and 0.05-2 parts of an accelerant, wherein the compound A has at least one group shown in the following formula (1): # imgabs0 #; the number average molecular weight of the compound A is 100 to 7000; the prepolymer B is obtained by prepolymerizing acenaphthylene or acenaphthylene derivatives and a compound C under the action of an initiator; wherein the acenaphthene or the acenaphthene derivative has at least one group represented by the following formula (2): # imgabs 1 #; wherein the compound C has at least one group as shown in the following formula (3): # imgabs2 #; wherein Y is selected from # imgabs 3 #, # imgabs 4 # or # imgabs 5 #. The invention provides a preparation method of the resin composition. The invention also provides an application of the resin composition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of printed circuit boards, and in particular relates to a resin composition for preparing a printed circuit board, and a preparation method and application thereof. Background Art

[0002] For the printed circuit board substrate materials used in server and router network-related equipment, with the high density and multi-layer, the board is required to have high heat resistance and through-hole reliability, and higher requirements are put forward for the glass transition temperature (Tg), XY-CTE, and Z-CTE of the board. It is expected that the thermal expansion coefficient (Z direction) is below 40ppm / ℃ and further below 35ppm / ℃. At present, the XY-CTE of commercial high-speed boards is generally 18-20ppm / ℃. To achieve higher reliability requirements, it is hoped that the XY-CTE can reach 13-15ppm / ℃, or even below 13ppm / ℃. At the same time, in order to maintain high-speed characteristics, it is required to meet lower dielectric constant and dielectric loss requirements at higher frequency bands.

[0003] Adding fillers to the resin composition is effective in reducing the thermal expansion coefficient, but the addition of fillers is limited in order to ensure the resin fluidity during circuit filling. Therefore, it is necessary to maintain a lower CTE performance even with a smaller amount of filler added.

[0004] In view of this, it is necessary to develop a resin composition for electronic materials that is stable in properties and can provide low expansion coefficient and dielectric properties. Summary of the invention

[0005] In view of this, the first object of the present invention is to provide a resin composition having low expansion coefficient, low dielectric constant, low dielectric loss and excellent heat resistance and good processability. The second object of the present invention is to provide a method for preparing the resin composition.

[0006] The third object of the present invention is to provide an application of the resin composition.

[0007] To achieve the above object, the present invention adopts the following technical solutions: A resin composition comprises, by weight, 20-60 parts of methacrylate-based modified polyphenylene ether resin, 40-80 parts of prepolymer and 0.05-2 parts of accelerator.

[0008] Relative to the total mass fraction of the aforementioned compound A and prepolymer B is 100 parts, and the mass fraction of resin compound A is preferably 20-60 parts, and more preferably 30-60 parts. In addition, relative to the total mass fraction of the aforementioned compound A and prepolymer B is 100 parts, the mass fraction of the aforementioned prepolymer B is preferably 40-80 parts, and more preferably 50-70 parts. In addition, relative to the total mass fraction of the aforementioned compound A and prepolymer B is 100 parts, and the content of the aforementioned accelerator is preferably 0.05-2 parts. If the contents of the aforementioned compound A, prepolymer B, and accelerator are all within the above range, a cured product with good dielectric properties, heat resistance, and anti-stripping properties can be obtained. It should be noted that the contents of the aforementioned compound A, prepolymer B, and accelerator are in the preferred range, and the specific ratio is not particularly limited.

[0009] Wherein, compound A has at least one group represented by the following formula (1): ; Among them, R 1 , R 2 , R 3 , R 4 each independently represents a hydrogen atom, an alkyl group, an arylene group or an aryl group; and The number average molecular weight of compound A is 100-7000; the resin compound A containing -C=C- double bonds can undergo free radical polymerization under appropriate conditions due to the presence of double bonds, and after reacting with a cross-linking agent containing one or more -C=C- double bonds, a thermosetting resin with three-dimensional network cross-linking can be formed. Preferably, the resin compound is a liquid with a number average molecular weight between 100-7000 or a resin compound that can be dissolved in a suitable solvent, which further ensures the processability of the product production process.

[0010] Compound A may be a modified polyphenylene ether compound having at least one molecular structure of the aforementioned formula (1) in its molecular structure, and a polymer having a unit of the following structure (5) in its molecule. Formula 5 is as follows: In formula (5), R 1 -R 4 , R 6 -R 8 All represent independent hydrogen atoms or hydrocarbon groups, that is, R 1 -R 4 , R 6 -R 8 They can be the same group or different groups. 6 -R 8 It is a hydrogen atom or a hydrocarbon group having 1 to 7 carbon atoms.

[0011] Compound A may have a group represented by formula (1), and the atoms bound by the group are not particularly limited, including but not limited to modified polyphenylene ether, styrene and its derivatives, divinylbenzene and its oligomers, acenaphthylene, butadiene / styrene / divinylbenzene and other low molecular weight or high molecular weight homopolymers or copolymers and their modified products, maleic anhydride imide compounds, etc. In addition, as compound A, the above compounds may be used alone or in combination of two or more.

[0012] Modified polyphenylene ether compounds The modified polyphenylene ether compound is not particularly limited as long as it has a group structure represented by the above formula (1) at a molecular terminal.

[0013] The modified polyphenylene ether compound has a polyphenylene ether chain in the molecule, and preferably has the following structural formula (6), and particularly preferably is the SA9000 model produced by Sabic.

[0014] Formula (6) In formula (6), m represents a range of 1-80. 9 -R 12 are hydrogen atoms or any other groups independently of each other. 9 -R 12 are independently hydrogen atoms or alkane groups.

[0015] The modified polyphenylene ether compound may be a graft-modified or block-modified compound of the structural unit of the formula (6) or a terminal-modified compound.

[0016] Furthermore, as the modified polyphenylene ether compound, the above compounds may be used alone or in combination of two or more.

[0017] The prepolymer B is obtained by prepolymerizing acenaphthylene or a derivative of acenaphthylene with compound C under the action of an initiator; Wherein, acenaphthylene or its derivative has at least one group represented by the following formula (2): ; Acenaphthylene is usually in the form of a solid monomer. During the manufacturing process of prepreg, acenaphthylene monomer is yellow and easily volatilizes during high-temperature drying. This not only causes problems such as gluing equipment and environmental pollution, but may also cause changes in the physical and chemical properties of the laminates subsequently produced, resulting in batch instability. Acenaphthylene contains a cyclic double bond structure. From its structure, it can be easily found that it can copolymerize with compounds containing unsaturated double bonds based on a free radical polymerization reaction of double bonds. Under certain conditions, acenaphthylene is subjected to a certain degree of copolymerization pretreatment to form a small molecule polymer. The oligomer itself is colorless and transparent, and its volatility point is significantly higher than that of acenaphthylene. It will not volatilize during the preparation process of the prepreg, which is easy to process and ensures the stability of the composition of the prepreg, thereby obtaining a back-end product with the same stable performance.

[0018] Furthermore, for the compound C containing unsaturated double bonds to be polymerized with acenaphthylene, in order to enable it to fully polymerize with acenaphthylene and the resulting copolymer still has excellent cross-linking reaction ability, it is preferred to use a compound containing unsaturated double bonds with two or more functionalities. At the same time, in order to obtain a polymer with excellent electrical properties, it is more preferred that the compound only contains alkane and ether structures and does not contain heteroatoms other than carbon / hydrogen / oxygen. In addition, in order to seek better dimensional stability, it is more preferred that the compound contain a benzene ring structure.

[0019] Wherein, compound C has at least one group represented by the following formula (3): ; Among them, Y is selected from , or ; where n 1 represents an integer from 0 to 30, n 2 represents an integer from 0 to 6, n 3 、n 4 、n 5 、n 6 and n 7 Each independently represents an integer from 1 to 6.

[0020] The compound A comprises methacrylate-modified polyphenylene ether resin, vinylbenzyl-modified polyphenylene ether resin, divinylbenzene oligomer, divinylbenzene or polybutadiene resin; The compound C includes p-divinylbenzeneethane, bis(vinylphenyl)dimethylenebenzene or bis(vinylphenyl)dimethylene ether.

[0021] The acenaphthylene compound and its derivatives and compound C need to be pretreated. The specific treatment method is to carry out polymerization reaction of the acenaphthylene compound and its derivatives and compound C under certain temperature / time conditions, with or without an initiator, to obtain a copolymer of the acenaphthylene compound and its derivatives and compound C, namely, prepolymer B.

[0022] The copolymerization of the acenaphthylene compound and its derivatives and compound C may be homopolymerization or block polymerization, without any special requirement.

[0023] There is no special requirement for the types of the acenaphthylene compound and its derivatives and compound C. The acenaphthylene compound and its derivatives can be one or more of the acenaphthylene compound and its derivatives. Compound C can be one or more of the compounds that meet the above requirements.

[0024] The mass fraction of the acenaphthylene compound and its derivatives and compound C is preferably 30-90 parts, and more preferably 50-90 parts, relative to the total mass fraction of the acenaphthylene compound and its derivatives and compound C is 100 parts. The mass fraction of the acenaphthylene compound and its derivatives and compound C is preferably 10-70 parts, and more preferably 10-50 parts.

[0025] The weight average molecular weight of the copolymer of acenaphthylene compound and its derivative and compound C is preferably 1000-5000, more preferably 1000-2000, and more preferably 1300-1700. If the weight average molecular weight is too low, there is a tendency that the volatility of the acenaphthylene compound and its derivative cannot be improved. If the weight average molecular weight is too high, there is a possibility that the viscosity of the resin composition increases, the melt viscosity during heat molding increases, and the moldability during heat molding decreases. Therefore, as long as the weight average molecular weight of the prepolymer B is within the above range, the production processability and product stability can be improved. It should be noted that the weight average molecular weight here is any value obtained by measuring the molecular weight by a conventional molecular weight measurement method. Specifically, the value measured by gel permeation chromatography (GPC) can be cited.

[0026] The average number of functional groups (functional group number) of the prepolymer B and the copolymer that contribute to the reaction with the compound A per molecule varies depending on the weight average molecular weight of the oligomer, and is preferably 2 to 20, and more preferably 2 to 18. If the number of functional groups is too small, it tends to be difficult to obtain a cured product having sufficient heat resistance. In addition, if the number of functional groups is too large, the reactivity becomes too high, and there is a risk of causing undesirable conditions such as reduced storage stability of the resin composition or reduced fluidity of the resin composition.

[0027] The ratio of acenaphthylene or acenaphthylene derivative to compound C is 3:7-9:1; The weight average molecular weight of the prepolymer is 1000-5000.

[0028] The accelerator includes an azo compound; The initiator includes a peroxy compound.

[0029] The azo compound includes azobisisobutyronitrile; The peroxygen compound includes benzoyl peroxide.

[0030] The method for preparing the resin composition comprises the steps of mixing compound A, prepolymer B and accelerator in a solvent and then drying.

[0031] The drying temperature is 100-180°C.

[0032] The resin composition is used to prepare prepreg; or Used in the preparation of films with resin; The prepreg comprises the resin composition and a fiber base material.

[0033] The fiber substrate includes glass cloth, aramid cloth, polyester cloth, glass non-woven fabric, aramid non-woven fabric, polyester non-woven fabric, pulp paper, or cotton woven fabric.

[0034] The application of the prepreg is used to prepare metal foil-clad laminates. The metal foil-clad laminate is used in preparing wiring boards.

[0035] The application of the prepreg is to prepare copper clad laminates; The copper clad laminate further includes an inorganic filler.

[0036] The inorganic filler includes silicon dioxide.

[0037] Other Ingredients The resin composition of the present invention may also be added with other ingredients other than the aforementioned compound A, prepolymer B and accelerator within the scope of not damaging the effect of the present invention. Other ingredients added to the resin composition of the present invention may include, but are not limited to, additives such as silane coupling agents, flame retardants, defoamers, antioxidants, heat stabilizers, antistatic agents, ultraviolet absorbers, dyes or pigments, lubricants and fillers. In addition, in the aforementioned resin composition, in addition to the resin compound A, thermosetting resins such as epoxy resins, unsaturated polyester resins, thermosetting polyimide resins, and unsaturated hydrocarbon resins may also be contained. As described above, a silane coupling agent may be included in the composition of the present invention. The aforementioned silane coupling agent may be included in the resin composition, preferably, it may be included in a manner of pretreating the surface of the filler, more preferably, it may be included in a manner of pretreating the surface of the filler, and at the same time, it may be included in the resin composition. In addition, in the prepreg, it may be included in a manner of pretreating the surface of the fibrous substrate.

[0038] The aforementioned silane coupling agent is a compound having one of vinyl, styryl, methacryloyl, acryloyl and phenylamino groups as a reactive group and having a hydrolyzable group such as methoxy or ethoxy, etc., without particular limitation. In addition, the aforementioned silane coupling agent may be used alone or in combination of two or more.

[0039] As described above, the composition of the present invention may contain a flame retardant. By containing a flame retardant, the flame retardancy of the cured product of the resin composition can be improved. The aforementioned flame retardant is not particularly limited. Including but not limited to halogen flame retardants, phosphorus flame retardants, nitrogen flame retardants, etc., for example, bromine halogen flame retardants such as decabromodiphenyl ether, hexabromobenzene, decabromodiphenyl ethane, ethylene bis tetrabromophthalimide, etc., for example, tris (2,6-dimethylphenyl) -phosphine, phenoxyphosphazene, xylene bis (diphenyl phosphine oxide), hypophosphite and other phosphorus flame retardants. In addition, as the aforementioned flame retardant, it can be used alone or in combination of two or more.

[0040] As mentioned above, the composition of the present invention may contain fillers such as inorganic fillers. As fillers, fillers added to improve the flame retardancy and heat resistance of the cured product of the composition can be listed, without special designation. Including but not limited to silicon dioxide such as spherical silica, metal oxides such as alumina, metal hydroxides such as aluminum hydroxide, aluminum borate, calcium carbonate, etc. As fillers, silicon dioxide, etc. are preferred, and spherical silica, etc. are more preferred. In addition, as the aforementioned filler, it can be used alone or in combination of two or more. In addition, as a filler, it can be used directly, and it can be used after surface treatment with a silane coupling agent. In particular, when it contains a filler, its filler content is preferably 30-270 parts by mass for the aforementioned composition, and more preferably 50-250 parts.

[0041] Preparation method There is no particular limitation on the method for producing the resin composition. That is, the method of mixing the compound A, the prepolymer B, and the accelerator in predetermined contents is not particularly limited.

[0042] For example, the resin composition is usually dissolved in a suitable solvent, and heating and other operations may be performed as needed, and the insoluble components are dispersed to a specified dispersion state with the assistance of a ball mill, a bead mill, a homogenizer, an emulsifier, and other equipment. In particular, the solvent is not particularly required as long as it can dissolve the resin compound A, the prepolymer B, and the accelerator and does not react with any of them or hinder the curing reaction of the resin composition.

[0043] After obtaining the resin composition of the present invention, further obtainable are: prepreg, metal foil-clad laminate, wiring board, metal foil with copper foil, and film with resin containing the resin composition of the present invention.

[0044] Prepreg The prepreg of the present invention should include: the aforementioned resin composition or the aforementioned semi-cured product of the resin composition and a fiber-based material.

[0045] The method for manufacturing the prepreg is not particularly limited as long as the aforementioned prepreg can be manufactured. For example, the aforementioned resin composition is formulated into a resin varnish and then attached to a fiber-based material by impregnation or coating.

[0046] The semi-cured product is a product in which the resin composition is partially cured and is in a state where further curing reaction is possible.

[0047] The semi-cured resin composition is obtained by naturally drying or heating the resin composition.

[0048] Specific examples of the fiber-based material include glass cloth, aramid cloth, polyester cloth, glass nonwoven fabric, aramid nonwoven fabric, polyester nonwoven fabric, pulp paper, and cotton woven fabric.

[0049] Glass cloth is preferred because it can provide the laminate with better mechanical properties. Meanwhile, fiber-opening treatment can improve uniformity, so fiber-opening treatment of glass cloth is more preferred.

[0050] Metal foil laminate The metal foil-clad laminate of the present invention should include: an insulating layer of the aforementioned cured resin composition or the aforementioned cured prepreg, and a metal foil coated on one or both sides of the surface of the insulating layer. In addition, the aforementioned metal foil is subject to actual needs, and its type and thickness are not particularly limited. The thickness of the metal foil can be preferably 0.1-105 μm, and the type of metal foil can include but is not limited to copper foil, aluminum foil, etc.

[0051] The method for producing the metal-clad laminate is not particularly limited as long as the metal-clad laminate can be produced. For example, the prepreg is coated with metal foil on both sides and cured under pressure and heating conditions.

[0052] In particular, the resin composition of the present invention can be used to produce a cured product of the resin composition having low dielectric properties and high heat resistance. Therefore, the metal-clad laminate having the resin composition of the present invention cured into an insulating layer is also a metal-clad laminate having low dielectric properties and high heat resistance.

[0053] Wiring board The wiring board of the present invention should include: a metal foil-clad laminate of the cured resin composition, and wiring formed by etching a portion of the metal foil on one side or both sides.

[0054] The method for manufacturing the wiring board is not particularly limited as long as it can manufacture the aforementioned wiring board.

[0055] The wiring board according to the present invention is a wiring board having low dielectric properties and high heat resistance.

[0056] Metal foil with resin The metal foil with resin of the present invention should include: an insulating layer of the aforementioned resin composition or a cured product of the aforementioned resin composition, and a metal foil.

[0057] The aforementioned insulating layer may or may not include a fiber base material as long as it includes the aforementioned resin composition or a cured product of the aforementioned resin composition.

[0058] The metal foil with resin may be covered with a release film as needed to prevent contamination and damage.

[0059] The release film is not particularly limited as long as it does not react with the insulating layer and can be separated from the insulating layer without remaining.

[0060] The method for producing the metal foil with resin is not particularly limited as long as it can produce the metal foil with resin. For example, the metal foil with resin can be obtained by coating the required content of the resin composition on the metal foil surface with a coater and then drying it.

[0061] Film with resin The resin-bearing film of the present invention should include: an insulating layer of the aforementioned resin composition or a cured product of the aforementioned resin composition, and a supporting film.

[0062] The aforementioned resin layer may contain the aforementioned resin composition or the aforementioned resin composition cured product, and may or may not contain a fiber base material.

[0063] The support film is not particularly limited as long as it does not react with the insulating layer and can be separated from the insulating layer without remaining.

[0064] The aforementioned film with resin may be covered with a release film as needed to prevent contamination and damage.

[0065] The method for producing the film with resin is not particularly limited as long as the film with resin can be produced. For example, the film can be obtained by coating the required content of the resin composition on the support film surface with a coater and then drying it.

[0066] The filling material includes but is not limited to silicon dioxide such as spherical silicon dioxide, metal oxides such as aluminum oxide, metal hydroxides such as aluminum hydroxide, aluminum borate, calcium carbonate, etc. As the filling material, silicon dioxide, etc. are preferred, and spherical silicon dioxide, etc. are more preferred. In addition, as the aforementioned filling material, it can be used alone or in combination of two or more. In addition, as a filler, it can be used directly, and can be used after surface treatment with a silane coupling agent. In particular, when containing a filler, its filler content is preferably 30-270 parts by mass for the aforementioned resin composition, and more preferably 50-250 parts.

[0067] Compared with the prior art, the present invention has the following beneficial effects: The present invention obtains a resin composition of a cured product with high heat resistance by cross-linking reaction between a resin compound and a prepolymer under the action of a promoter. Since there are no high polarity bonds such as ether bonds and CN in the prepolymer, a resin composition with low dielectric constant and low dielectric loss can be obtained. Moreover, since acenaphthylene has a certain compressibility after prepolymerization, the thermal expansion coefficient of the obtained resin composition is greatly reduced. DETAILED DESCRIPTION

[0068] The present invention is further described below by way of examples, but the protection scope of the present invention is not limited by the following examples.

[0069] The material statistics table involved in the specific embodiment of the present invention is as follows Table 1 Table 1 Specifically, the prepreg provided by the present invention is prepared by the following method: dissolving compound A, prepolymer B, accelerator and other series of auxiliary agents in a mixed solvent of toluene and ketones, fully stirring and adjusting to a suitable viscosity, impregnating the resin glue with 2116 glass fiber cloth to make the unit weight reach a suitable value, and drying in an oven at 140° C. for 5 minutes to remove the toluene and ketone solvents to obtain the 2116 prepreg.

[0070] Specifically, the high-speed copper-clad laminate provided by the present invention is prepared by the following method: Dissolve compound A, prepolymer B, accelerator and other series of additives in toluene and ketone mixed solvent, stir thoroughly and adjust to suitable viscosity, soak 2116 glass fiber cloth in resin glue to make the unit weight suitable, dry in oven at 140℃ for 5min, remove toluene and ketone solvents, and obtain 2116 prepreg. Overlap 6 sheets of 2116 prepreg, with copper foil of HoZ thickness on the upper and lower sides, vacuum laminate and cure for 125min in a press, with curing pressure of 2MPa and curing temperature of 220℃, to obtain high-speed copper clad laminate.

[0071] The present invention is further described below in conjunction with specific embodiments.

[0072] Example 1 Dissolve 40 parts of SA9000, 60 parts of prepolymer, 0.5 parts of VR-110, and 60 parts of spherical silica in toluene, stir thoroughly and adjust to a suitable viscosity, soak the resin glue with 2116 glass fiber cloth to make the unit weight appropriate, and dry it in an oven at 140°C for 5 minutes, remove the toluene, and obtain 2116 prepreg. Overlap 6 sheets of 2116 prepreg, and coat the upper and lower surfaces with copper foil of HoZ thickness, vacuum laminate and cure for 125 minutes in a press, with a curing pressure of 2MPa and a curing temperature of 220°C to obtain a high-speed copper clad laminate.

[0073] Wherein, the preparation method of prepolymer B is as follows: After mixing erene and BVPE in a weight ratio of 1:1, 0.15 wt% DCP and a certain amount of solvent (toluene) were added and mixed at 60° C., and reacted for 2 hours to obtain a prepolymer.

[0074] Example 2 Dissolve 40 parts of SA9000, 60 parts of prepolymer, 0.5 parts of VR-110, and 60 parts of spherical silica in toluene, stir thoroughly and adjust to a suitable viscosity, soak the resin glue with 2116 glass fiber cloth to make the unit weight appropriate, and dry it in an oven at 140°C for 5 minutes, remove the toluene, and obtain 2116 prepreg. Overlap 6 sheets of 2116 prepreg, and coat the upper and lower surfaces with copper foil of HoZ thickness, vacuum laminate and cure for 125 minutes in a press, with a curing pressure of 2MPa and a curing temperature of 220°C to obtain a high-speed copper clad laminate.

[0075] Wherein, the preparation method of prepolymer B is as follows: After mixing ersene and BVPE in a weight ratio of 1:1, 0.15 wt% DCP and a certain amount of solvent were added, mixed at 70° C., and reacted for 2 hours to obtain a prepolymer.

[0076] Example 3 Dissolve 40 parts of SA9000, 60 parts of prepolymer, 0.5 parts of VR-110, and 60 parts of spherical silica in toluene, stir thoroughly and adjust to a suitable viscosity, soak the resin glue with 2116 glass fiber cloth to make the unit weight appropriate, and dry it in an oven at 140°C for 5 minutes, remove the toluene, and obtain 2116 prepreg. Overlap 6 sheets of 2116 prepreg, and coat the upper and lower surfaces with copper foil of HoZ thickness, vacuum laminate and cure for 125 minutes in a press, with a curing pressure of 2MPa and a curing temperature of 220°C to obtain a high-speed copper clad laminate.

[0077] Wherein, the preparation method of prepolymer B is as follows: After mixing erene and BVPE in a weight ratio of 1:1, 0.15 wt% DCP and a certain amount of solvent were added, mixed at 80° C., and reacted for 2 hours to obtain a prepolymer.

[0078] Example 4 Dissolve 40 parts of SA9000, 60 parts of prepolymer, 0.5 parts of VR-110, and 60 parts of spherical silica in toluene, stir thoroughly and adjust to a suitable viscosity, soak the resin glue with 2116 glass fiber cloth to make the unit weight appropriate, and dry it in an oven at 140°C for 5 minutes, remove the toluene, and obtain 2116 prepreg. Overlap 6 sheets of 2116 prepreg, and coat the upper and lower surfaces with copper foil of HoZ thickness, vacuum laminate and cure for 125 minutes in a press, with a curing pressure of 2MPa and a curing temperature of 220°C to obtain a high-speed copper clad laminate.

[0079] Wherein, the preparation method of prepolymer B is as follows: After mixing erlenme and BVPE in a weight ratio of 1:1, 0.15 wt% DCP and a certain amount of solvent were added, mixed at 90° C., and reacted for 2 hours to obtain a prepolymer.

[0080] Example 5 Dissolve 40 parts of SA9000, 60 parts of prepolymer, 0.5 parts of VR-110, and 60 parts of spherical silica in toluene, stir thoroughly and adjust to a suitable viscosity, soak the resin glue with 2116 glass fiber cloth to make the unit weight appropriate, and dry it in an oven at 140°C for 5 minutes, remove the toluene, and obtain 2116 prepreg. Overlap 6 sheets of 2116 prepreg, and coat the upper and lower surfaces with copper foil of HoZ thickness, vacuum laminate and cure for 125 minutes in a press, with a curing pressure of 2MPa and a curing temperature of 220°C to obtain a high-speed copper clad laminate.

[0081] Wherein, the preparation method of prepolymer B is as follows: After erene and BVPE were mixed at a weight ratio of 1:1, 0.15 wt% DCP and a certain amount of solvent were added, mixed at 100° C., and reacted for 2 hours to obtain a prepolymer.

[0082] Example 6 Dissolve 40 parts of SA9000, 60 parts of prepolymer, 0.5 parts of VR-110, and 60 parts of spherical silica in toluene, stir thoroughly and adjust to a suitable viscosity, soak the resin glue with 2116 glass fiber cloth to make the unit weight appropriate, and dry it in an oven at 140°C for 5 minutes, remove the toluene, and obtain 2116 prepreg. Overlap 6 sheets of 2116 prepreg, and coat the upper and lower surfaces with copper foil of HoZ thickness, vacuum laminate and cure for 125 minutes in a press, with a curing pressure of 2MPa and a curing temperature of 220°C to obtain a high-speed copper clad laminate.

[0083] Wherein, the preparation method of prepolymer B is as follows: After mixing erlenme and BVPE at a weight ratio of 1:1, 0.15wt% DCP and some solvent were added and mixed at 110°C and reacted for 2h to obtain a prepolymer. Example 7 Dissolve 40 parts of SA9000, 60 parts of prepolymer, 0.5 parts of VR-110, and 60 parts of spherical silica in toluene, stir thoroughly and adjust to a suitable viscosity, soak the resin glue with 2116 glass fiber cloth to make the unit weight appropriate, and dry it in an oven at 140°C for 5 minutes, remove the toluene, and obtain 2116 prepreg. Overlap 6 sheets of 2116 prepreg, and coat the upper and lower surfaces with copper foil of HoZ thickness, vacuum laminate and cure for 125 minutes in a press, with a curing pressure of 2MPa and a curing temperature of 220°C to obtain a high-speed copper clad laminate.

[0084] Wherein, the preparation method of prepolymer B is as follows: After mixing erlenme and BVPE at a weight ratio of 1:1, 0.15wt% DCP and some solvent were added and mixed at 80°C for 1h to obtain a prepolymer. Example 8 Dissolve 40 parts of SA9000, 60 parts of prepolymer, 0.5 parts of VR-110, and 60 parts of spherical silica in toluene, stir thoroughly and adjust to a suitable viscosity, soak the resin glue with 2116 glass fiber cloth to make the unit weight appropriate, and dry it in an oven at 140°C for 5 minutes, remove the toluene, and obtain 2116 prepreg. Overlap 6 sheets of 2116 prepreg, and coat the upper and lower surfaces with copper foil of HoZ thickness, vacuum laminate and cure for 125 minutes in a press, with a curing pressure of 2MPa and a curing temperature of 220°C to obtain a high-speed copper clad laminate.

[0085] Wherein, the preparation method of prepolymer B is as follows: After mixing erlenme and BVPE in a weight ratio of 1:1, 0.15 wt% DCP and a certain amount of solvent were added, mixed at 80° C., and reacted for 3 hours to obtain a prepolymer.

[0086] Example 9 Dissolve 40 parts of SA9000, 60 parts of prepolymer, 0.5 parts of VR-110, and 60 parts of spherical silica in toluene, stir thoroughly and adjust to a suitable viscosity, soak the resin glue with 2116 glass fiber cloth to make the unit weight appropriate, and dry it in an oven at 140°C for 5 minutes, remove the toluene, and obtain 2116 prepreg. Overlap 6 sheets of 2116 prepreg, and coat the upper and lower surfaces with copper foil of HoZ thickness, vacuum laminate and cure for 125 minutes in a press, with a curing pressure of 2MPa and a curing temperature of 220°C to obtain a high-speed copper clad laminate.

[0087] Wherein, the preparation method of prepolymer B is as follows: After ersene and BVPE were mixed at a weight ratio of 1:1, 0.15 wt% DCP and a certain amount of solvent were added, mixed at 80° C., and reacted for 4 hours to obtain a prepolymer.

[0088] Example 10 Dissolve 20 parts of SA9000, 80 parts of prepolymer, 0.5 parts of VR-110, and 60 parts of spherical silica in toluene, stir thoroughly and adjust to a suitable viscosity, soak the resin glue with 2116 glass fiber cloth to make the unit weight appropriate, and dry it in an oven at 140°C for 5 minutes, remove the toluene, and obtain 2116 prepreg. Overlap 6 sheets of 2116 prepreg, and coat the upper and lower surfaces with copper foil of HoZ thickness, vacuum laminate and cure for 125 minutes in a press, with a curing pressure of 2MPa and a curing temperature of 220°C to obtain a high-speed copper clad laminate.

[0089] Wherein, the preparation method of prepolymer B is as follows: After mixing erene and BVPE in a weight ratio of 1:1, 0.15 wt% DCP and a certain amount of solvent were added, mixed at 80° C., and reacted for 2 hours to obtain a prepolymer.

[0090] Embodiment 11 Dissolve 40 parts of OPE-2ST, 60 parts of prepolymer, 0.5 parts of VR-110, and 60 parts of spherical silica in toluene, stir thoroughly and adjust to a suitable viscosity, soak the resin glue with 2116 glass fiber cloth to make the unit weight appropriate, and dry it in an oven at 140°C for 5 minutes, remove toluene, and obtain 2116 prepreg. Overlap 6 sheets of 2116 prepreg, and coat the upper and lower surfaces with copper foil of HoZ thickness, vacuum laminate and cure for 125 minutes in a press, with a curing pressure of 2MPa and a curing temperature of 220°C to obtain a high-speed copper clad laminate.

[0091] Wherein, the preparation method of prepolymer B is as follows: After mixing erene and BVPE in a weight ratio of 1:1, 0.15 wt% DCP and a certain amount of solvent were added, mixed at 80° C., and reacted for 2 hours to obtain a prepolymer.

[0092] Example 12 Dissolve 40 parts of OPE-2ST (2200), 60 parts of prepolymer, 0.5 parts of VR-110, and 60 parts of spherical silica in toluene, stir thoroughly and adjust to a suitable viscosity, soak the resin glue with 2116 glass fiber cloth to make the unit weight appropriate, and dry it in an oven at 140°C for 5 minutes, remove toluene, and obtain 2116 prepreg. Overlap 6 sheets of 2116 prepreg, and coat the upper and lower surfaces with copper foil of HoZ thickness, vacuum laminate and cure for 125 minutes in a press, with a curing pressure of 2MPa and a curing temperature of 220°C to obtain a high-speed copper clad laminate.

[0093] Wherein, the preparation method of prepolymer B is as follows: After mixing erene and BVPE in a weight ratio of 1:1, 0.15 wt% DCP and a certain amount of solvent were added, mixed at 80° C., and reacted for 2 hours to obtain a prepolymer.

[0094] Embodiment 13 Dissolve 40 parts of ODV-EXT (X04), 60 parts of prepolymer, 0.5 parts of VR-110, and 60 parts of spherical silica in toluene, stir thoroughly and adjust to a suitable viscosity, soak the resin glue with 2116 glass fiber cloth to make the unit weight appropriate, and dry it in an oven at 140°C for 5 minutes, remove toluene, and obtain 2116 prepreg. Overlap 6 sheets of 2116 prepreg, and coat the upper and lower surfaces with copper foil of HoZ thickness, vacuum laminate and cure for 125 minutes in a press, with a curing pressure of 2MPa and a curing temperature of 220°C to obtain a high-speed copper clad laminate.

[0095] Wherein, the preparation method of prepolymer B is as follows: After mixing erene and BVPE in a weight ratio of 1:1, 0.15 wt% DCP and a certain amount of solvent were added, mixed at 80° C., and reacted for 2 hours to obtain a prepolymer.

[0096] Embodiment 14 Dissolve 20 parts of B-1000, 80 parts of prepolymer, 0.5 parts of VR-110, and 60 parts of spherical silica in toluene, stir thoroughly and adjust to a suitable viscosity, soak the resin glue with 2116 glass fiber cloth to make the unit weight appropriate, and dry it in an oven at 140°C for 5 minutes, remove toluene, and obtain 2116 prepreg. Overlap 6 sheets of 2116 prepreg, and coat the upper and lower surfaces with copper foil of HoZ thickness, vacuum laminate and cure for 125 minutes in a press, with a curing pressure of 2MPa and a curing temperature of 220°C to obtain a high-speed copper clad laminate.

[0097] Wherein, the preparation method of prepolymer B is as follows: After mixing erene and BVPE in a weight ratio of 1:1, 0.15 wt% DCP and a certain amount of solvent were added, mixed at 80° C., and reacted for 2 hours to obtain a prepolymer.

[0098] Embodiment 15 Dissolve 20 parts of DVB, 80 parts of prepolymer, 0.5 parts of VR-110, and 60 parts of spherical silica in toluene, stir thoroughly and adjust to a suitable viscosity, soak the resin glue with 2116 glass fiber cloth to make the unit weight appropriate, and dry it in an oven at 140°C for 5 minutes, remove the toluene, and obtain 2116 prepreg. Overlap 6 sheets of 2116 prepreg, and coat the upper and lower surfaces with copper foil of HoZ thickness, vacuum laminate and cure for 125 minutes in a press, with a curing pressure of 2MPa and a curing temperature of 220°C to obtain a high-speed copper clad laminate.

[0099] Wherein, the preparation method of prepolymer B is as follows: After mixing erene and BVPE in a weight ratio of 1:1, 0.15 wt% DCP and a certain amount of solvent were added, mixed at 80° C., and reacted for 2 hours to obtain a prepolymer.

[0100] Example 16 Dissolve 20 parts of SA9000, 20 parts of ODV-EXT (X04), 60 parts of prepolymer, 0.5 parts of VR-110, and 60 parts of spherical silica in toluene, stir thoroughly and adjust to a suitable viscosity, soak the resin glue with 2116 glass fiber cloth to make the unit weight appropriate, and dry it in an oven at 140°C for 5 minutes, remove toluene, and obtain 2116 prepreg. Overlap 6 sheets of 2116 prepreg, and coat the upper and lower surfaces with copper foil of HoZ thickness, vacuum laminate and cure for 125 minutes in a press, with a curing pressure of 2MPa and a curing temperature of 220°C to obtain a high-speed copper clad laminate.

[0101] Wherein, the preparation method of prepolymer B is as follows: After mixing erene and BVPE in a weight ratio of 1:1, 0.15 wt% DCP and a certain amount of solvent were added, mixed at 80° C., and reacted for 2 hours to obtain a prepolymer.

[0102] Embodiment 17 Dissolve 40 parts of SA9000, 60 parts of prepolymer, 0.05 parts of VR-110, and 60 parts of spherical silica in toluene, stir thoroughly and adjust to a suitable viscosity, soak the resin glue with 2116 glass fiber cloth to make the unit weight appropriate, and dry it in an oven at 140°C for 5 minutes, remove toluene, and obtain 2116 prepreg. Overlap 6 sheets of 2116 prepreg, and coat the upper and lower surfaces with copper foil of HoZ thickness, vacuum laminate and cure for 125 minutes in a press, with a curing pressure of 2MPa and a curing temperature of 220°C to obtain a high-speed copper clad laminate.

[0103] Wherein, the preparation method of prepolymer B is as follows: After mixing erene and BVPE in a weight ratio of 1:1, 0.15 wt% DCP and a certain amount of solvent were added, mixed at 80° C., and reacted for 2 hours to obtain a prepolymer.

[0104] Embodiment 18 Dissolve 40 parts of SA9000, 60 parts of prepolymer, 2 parts of VR-110, and 60 parts of spherical silica in toluene, stir thoroughly and adjust to a suitable viscosity, soak the resin glue with 2116 glass fiber cloth to make the unit weight appropriate, and dry it in an oven at 140°C for 5 minutes, remove toluene, and obtain 2116 prepreg. Overlap 6 sheets of 2116 prepreg, and coat the upper and lower surfaces with copper foil of HoZ thickness, vacuum laminate and cure for 125 minutes in a press, with a curing pressure of 2MPa and a curing temperature of 220°C to obtain a high-speed copper clad laminate.

[0105] Wherein, the preparation method of prepolymer B is as follows: After mixing erene and BVPE in a weight ratio of 1:1, 0.15 wt% DCP and a certain amount of solvent were added, mixed at 80° C., and reacted for 2 hours to obtain a prepolymer.

[0106] Embodiment 19 Dissolve 40 parts of SA9000, 60 parts of prepolymer, 0.5 parts of VR-110, and 60 parts of spherical silica in toluene, stir thoroughly and adjust to a suitable viscosity, soak the resin glue with 2116 glass fiber cloth to make the unit weight appropriate, and dry it in an oven at 140°C for 5 minutes, remove the toluene, and obtain 2116 prepreg. Overlap 6 sheets of 2116 prepreg, and coat the upper and lower surfaces with copper foil of HoZ thickness, vacuum laminate and cure for 125 minutes in a press, with a curing pressure of 2MPa and a curing temperature of 220°C to obtain a high-speed copper clad laminate.

[0107] Wherein, the preparation method of prepolymer B is as follows: After mixing erene and BVPE in a weight ratio of 9:1, 0.15wt% DCP and a certain amount of solvent were added, mixed at 80°C, and reacted for 2h to obtain a prepolymer.

[0108] Embodiment 20 Dissolve 40 parts of SA9000, 60 parts of prepolymer, 0.5 parts of VR-110, and 60 parts of spherical silica in toluene, stir thoroughly and adjust to a suitable viscosity, soak the resin glue with 2116 glass fiber cloth to make the unit weight appropriate, and dry it in an oven at 140°C for 5 minutes, remove the toluene, and obtain 2116 prepreg. Overlap 6 sheets of 2116 prepreg, and coat the upper and lower surfaces with copper foil of HoZ thickness, vacuum laminate and cure for 125 minutes in a press, with a curing pressure of 2MPa and a curing temperature of 220°C to obtain a high-speed copper clad laminate.

[0109] Wherein, the preparation method of prepolymer B is as follows: After mixing erlenme and BVPE in a weight ratio of 3:7, 0.15wt% DCP and a certain amount of solvent were added, mixed at 80°C, and reacted for 2h to obtain a prepolymer.

[0110] Comparative Example 1 Dissolve 40 parts of SA9000, 30 parts of BVPE, 30 parts of acenaphthylene, 0.5 parts of VR-110, and 60 parts of spherical silica in toluene, stir thoroughly and adjust to a suitable viscosity, soak the resin glue with 2116 glass fiber cloth to make the unit weight appropriate, and dry it in an oven at 140°C for 5 minutes, remove toluene, and obtain 2116 prepreg. Overlap 6 sheets of 2116 prepreg, and coat the upper and lower surfaces with copper foil of HoZ thickness, vacuum laminate and cure for 125 minutes in a press, with a curing pressure of 2MPa and a curing temperature of 220°C to obtain a high-speed copper clad laminate.

[0111] Comparative Example 2 Dissolve 40 parts of SA9000, 60 parts of prepolymer, 0.5 parts of VR-110, and 60 parts of spherical silica in toluene, stir thoroughly and adjust to a suitable viscosity, soak the resin glue with 2116 glass fiber cloth to make the unit weight appropriate, and dry it in an oven at 140°C for 5 minutes, remove the toluene, and obtain 2116 prepreg. Overlap 6 sheets of 2116 prepreg, and coat the upper and lower surfaces with copper foil of HoZ thickness, vacuum laminate and cure for 125 minutes in a press, with a curing pressure of 2MPa and a curing temperature of 220°C to obtain a high-speed copper clad laminate.

[0112] Wherein, the preparation method of prepolymer B is as follows: After ersene and TAIC were mixed at a weight ratio of 1:1, 0.15 wt% DCP and a certain amount of solvent were added, mixed at 80° C., and reacted for 2 hours to obtain a prepolymer.

[0113] Comparative Example 3 Dissolve 40 parts of SA9000, 60 parts of prepolymer, 0.5 parts of VR-110, and 60 parts of spherical silica in toluene, stir thoroughly and adjust to a suitable viscosity, soak the resin glue with 2116 glass fiber cloth to make the unit weight appropriate, and dry it in an oven at 140°C for 5 minutes, remove the toluene, and obtain 2116 prepreg. Overlap 6 sheets of 2116 prepreg, and coat the upper and lower surfaces with copper foil of HoZ thickness, vacuum laminate and cure for 125 minutes in a press, with a curing pressure of 2MPa and a curing temperature of 220°C to obtain a high-speed copper clad laminate.

[0114] Wherein, the preparation method of prepolymer B is as follows: After ersene and BMI-70 were mixed at a weight ratio of 1:1, 0.15 wt% DCP and a certain amount of solvent were added, mixed at 80° C., and reacted for 2 hours to obtain a prepolymer.

[0115] Comparative Example 4 Dissolve 40 parts of SA9000, 60 parts of prepolymer, 0.5 parts of VR-110, and 60 parts of spherical silica in toluene, stir thoroughly and adjust to a suitable viscosity, soak the resin glue with 2116 glass fiber cloth to make the unit weight appropriate, and dry it in an oven at 140°C for 5 minutes, remove the toluene, and obtain 2116 prepreg. Overlap 6 sheets of 2116 prepreg, and coat the upper and lower surfaces with copper foil of HoZ thickness, vacuum laminate and cure for 125 minutes in a press, with a curing pressure of 2MPa and a curing temperature of 220°C to obtain a high-speed copper clad laminate.

[0116] Wherein, the preparation method of prepolymer B is as follows: After mixing erlenme and BVPE in a weight ratio of 2:8, 0.15wt% DCP and a certain amount of solvent were added, mixed at 80°C, and reacted for 2h to obtain a prepolymer.

[0117] The high-speed copper-clad laminates prepared in the examples and comparative examples are tested below. The test results are shown in Tables 2 to 5. The specific testing method of the high-speed copper-clad laminate prepared in the specific embodiment of the invention is as follows: Glass transition temperature (DMA) (Tg) The Tg of the prepreg was measured using a dynamic thermomechanical analyzer "DMA850" manufactured by TA. At this time, the dynamic viscoelasticity measurement (DMA) was performed with the frequency set to 1 Hz in the bending modulus, and the temperature at which tanδ showed a maximum when the temperature was raised from room temperature to 300°C at a heating rate of 5°C / min was set as Tg. The measured data are shown in Tables 2 to 5.

[0118] Copper foil peel strength When making the aforementioned evaluation substrate, the number of overlapping prepreg sheets was set to 6, thereby obtaining a copper-clad laminate (metal-clad laminate) having a thickness of about 0.8 mm and a copper foil with a thickness of 18 μm bonded to both sides. The copper foils on both sides of the formed copper-clad laminate were treated with 3 mm characteristic tape, the remaining copper foils were removed by etching, and the samples were tested using a peel strength tester, and the measured data are shown in Tables 2 to 5.

[0119] Heat resistance (TMA method: T-300) When making the aforementioned evaluation substrate, the number of overlapping prepreg sheets was set to 6, thereby obtaining a copper-clad laminate (metal-clad laminate) having a thickness of about 0.8 mm and a copper foil with a thickness of 18 μm bonded on both sides. According to IPC-TM-650, the delamination burst time at 300°C was measured to evaluate the heat resistance of the aforementioned evaluation substrate, and the measured data are shown in Tables 2 to 5.

[0120] Water absorption Using a high-pressure accelerated aging tester, at 2MPa and 120°C, the water absorption rate after 180min of moisture absorption was measured. The measured data are shown in Tables 2 to 5.

[0121] Dielectric loss factor The dielectric loss factor of the evaluation substrate at 15 GHz was measured using a resonant cavity perturbation method. Specifically, a network analyzer (E5071C manufactured by Keysight Technologies) was used to measure the dielectric loss factor of the evaluation substrate at 15 GHz. The measured data are shown in Tables 2 to 5.

[0122] Prepreg surface The semi-cured sheet was visually inspected for smoothness and particle presence. The results are shown in Tables 2 to 5 below.

[0123] ZCTE When making the above-mentioned evaluation substrate, the number of overlapping prepregs is set to 6, thereby obtaining a copper-clad laminate (metal foil-clad laminate) with a thickness of about 0.8 mm and a copper foil with a thickness of 18 um bonded on both sides. The copper foil on both sides of the formed copper-clad laminate was removed by etching. For the evaluation laminate thus obtained, the thermal expansion coefficient based on the TMA method was evaluated according to IPCTM650. A thermomechanical analysis (TMA) device (TMAQ400 manufactured by TA) was used in the measurement, and the measurement was carried out in the range of 50-260°C. The measured data are shown in Tables 2-5.

[0124] XYCTE[Flow rate] Four sheets of 100*100mm prepreg were overlapped and the data were measured at 171°C, 5 minutes and 200psi and are shown in Tables 2 to 5 below.

[0125] Table 2 Table 3 Table 4 Table 5 It can be seen from Table 2 that (Examples 1-6) when different prepolymerization temperatures are used, the higher the prepolymerization temperature, the better the degree of crosslinking of the prepolymer, with a trend of higher Tg and PS, lower Df, water absorption, Rf, Z, and XYCTE, and better heat resistance. In general, the performance is better when the prepolymerization temperature is 60-110°C.

[0126] As shown in Table 2 (Examples 3, 7-8), when different prepolymerization times are used, the longer the prepolymerization time, the better the prepolymerization, with higher Tg and PS, and lower Df, water absorption, Rf, Z, and XYCTE. However, the performance is relatively good after 1-4 hours. In general, the performance is better at the prepolymerization temperature of 2 hours, and the fluidity has deteriorated at 4 hours, and the improvement of other properties is small, and the energy consumption is relatively large in actual production.

[0127] It can be seen from Table 2 and Table 3 that (Examples 3, 10, and 11) that when the weight ratio of resin compound A to prepolymer B is 40:60, the performance is optimal, and a high prepolymer content has excellent performance in Df, Z, XYCTE, and water absorption, but poor PS and Rf.

[0128] It can be seen from Table 2 and Table 4 that (Examples 3, 17-18) that when the amount of the above accelerator is too small, the reactivity is poor, the degree of resin curing is low, and Z, XYCTE, Tg, and T300 all deteriorate to a certain extent. When the amount of the above accelerator is too high, Tg, T300 and Df all tend to deteriorate.

[0129] It can be seen from Table 2 and Table 5 that: (Example 3, Comparative Example 1), that is, without using the copolymerization method, BVPE has precipitated particles, the PP appearance is poor, and the performance is worse than that of Example 3 using the copolymerization group.

[0130] It can be seen from Table 2 and Table 5 that (Example 3, Comparative Example 2-3) that the prepolymer B using the copolymer of BVPE and acenaphthylene has better comprehensive performance than TAIC and BMI-70.

[0131] It can be seen from Table 2 and Table 5 that (Example 3, Comparative Example 4) that when BVPE is excessive, particles will precipitate and the PP appearance will be poor. When acenaphthylene is excessive, PS and fluidity will be poor.

[0132] In order to describe the present invention, the present invention has been appropriately and fully described above through the embodiments, but it should be recognized that those skilled in the art can easily change and improve the above embodiments. Therefore, as long as the modified embodiments or improved embodiments implemented by those skilled in the art do not deviate from the scope of the rights of the claims recorded in the claims, the modified embodiments or improved embodiments can be interpreted as being included in the scope of the rights of the claims.

Claims

1. A resin composition, characterized in that: In parts by weight, it comprises 20-60 parts of compound A, 40-80 parts of prepolymer B and 0.05-2 parts of accelerator; Wherein, compound A has at least one group represented by the following formula (1): ; wherein R1, R2, R3, and R4 each independently represent a hydrogen atom, an alkyl group, an arylene group, or an aryl group; and The number average molecular weight of compound A is 100-7000; The prepolymer B is obtained by prepolymerizing acenaphthylene or a derivative of acenaphthylene with compound C under the action of an initiator; Wherein, acenaphthylene or its derivative has at least one group represented by the following formula (2): ; Wherein, compound C has at least one group represented by the following formula (3): ; Among them, Y is selected from , or ; wherein n1 represents an integer from 0 to 30, n2 represents an integer from 0 to 6, and n3, n4, n5, n6 and n7 each independently represent an integer from 1 to 6.

2. The resin composition according to claim 1, characterized in that: The compound A comprises methacrylate-modified polyphenylene ether resin, vinylbenzyl-modified polyphenylene ether resin, divinylbenzene oligomer, divinylbenzene or polybutadiene resin; The compound C comprises p-divinylbenzene ethane, bis(vinylphenyl)dimethylenebenzene or bis(vinylphenyl)dimethylene ether; The ratio of acenaphthylene or acenaphthylene derivative to compound C is 3:7-9:1; The weight average molecular weight of the prepolymer is 1000-5000.

3. The resin composition according to claim 1, wherein: The accelerator includes an azo compound; The initiator comprises a peroxide compound; The azo compound includes azobisisobutyronitrile; The peroxygen compound includes benzoyl peroxide.

4. The method for preparing a resin composition according to claim 1, wherein: The method comprises the steps of mixing compound A, prepolymer B and accelerator in a solvent and then drying.

5. The resin composition according to claim 1, wherein: The drying temperature is 100-180°C.

6. The use of the resin composition according to claim 1, characterized in that: Used in the preparation of prepreg; or Used in the preparation of films with resin; The prepreg comprises the resin composition and a fiber base material.

7. The use of the resin composition according to claim 6, characterized in that: The fiber substrate includes glass cloth, aramid cloth, polyester cloth, glass non-woven fabric, aramid non-woven fabric, polyester non-woven fabric, pulp paper, or cotton woven fabric.

8. The use of the prepreg according to claim 6, characterized in that: Used in the preparation of metal foil-clad laminates.

9. The use of the metal foil-clad laminate according to claim 1, characterized in that: Used in the preparation of wiring boards.

10. The use of the prepreg according to claim 6, characterized in that: Used in the preparation of copper clad laminates; The copper clad laminate further includes an inorganic filler; The inorganic filler includes silicon dioxide.

Citation Information

Cited By

  • Resin composition, prepreg and application of prepreg in rigid-flex printed circuit board

    CN121517885A